DEGRADASI STOK KARBON (C) AKIBAT ALIH GUNA LAHAN HUTAN MENJADI LAHAN KAKAO DI DAS NOPU, SULAWESI TENGAH - Anthon Monde (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
Forest conversion has caused carbon stock to decrease, both in vegetation/crop and in soil.  This research aimed to determine the impact of forest conversion to cocoa land use on vegetation and soil carbon stock in Nopu watershed Central Sulawesi. Results of the research showed that the forest conversion to cocoa land use has led to carbon stock decrease both in vegetation and in soil. The carbon stock has yet to fully recover in the 12 years old cacao plantation under agro-forestry system